Uji Stabilitas Fisik Facial Wash Gel Ekstrak Daun Mengkudu (Morinda citrifolia L.) Dengan Variasi Carbopolol Sebagai Gelling Agent - Eva Natalia; Maulita Saraswati; Supriyanto (Joseph: Journal of Science and Pharmacy, 2025)
Background: Noni leaves (Morinda citrifolia L.) are a plant with antibacterial properties. One of the most commonly used antibacterial cosmetic preparations is facial wash gel. Purpose: This study aims to formulate a facial wash gel preparation containing noni leaf extract (Morinda citrifolia L.) which has antibacterial content with variations of carbopolol.. Method: Noni leaf extract (Morinda citrifolia L.) was macerated with 96% ethanol solvent and tested for specific parameters in the form of organoleptic, ethanol-free, phyrochemical screening, and Thin Layer Chromatography tests and non-specific parameters in the form of drying loss. Then tested for physical quality, organoleptic test, homogeneity, pH, foam stability, viscosity, adhesive power. Then tested for physical stability for 6 cycles with 2 temperatures, 4 ° Celsius and 40 ° Celsius. with carbopolol concentrations of 0.5%, 1%, 1.5%, and 2%. Results: The research results showed that noni leaf extract can be used as a facial wash gel and contains flavonoids, alkaloids, terpenoids, and saponins. The noni leaf extract (Morinda citrifolia L.) facial wash gel produced good quality and physical stability. The best facial wash gel was formula three (2% carbopolol concentration). Conclusion: Noni leaf extract (Morinda citrifolia L.) can be made into a facial wash gel with good quality and physical stability and produces the best facial wash gel formula in the FIII preparation (2% carbopolol concentration).